PELATIHAN DESAIN KEMASAN (PACKAGING) DAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK UMKM KAPANEWON TURI - Bahri Bahri; Niken Permata Sari; Fikri Alamsyah (LP2M Universitas Ibrahimy, 2023)
The product development strategy is carried out by the innovation of packaging sizes (variations in price, size, and appearance); Packaging Color Innovation (light blue, red, green, purple, and yellow); Innovation of Packaging Materials (cans, aluminum, glass, plastic paper, boxes, and jars); Packaging Label Innovation (selection of colors, illustrations, letters, images); and Packaging Shape Innovation (graphic design, shape, and size). Digital marketing is done through Tokopedia's e-commerce. The pre-test results were dominated by 14 members or 32% did not understand how to design product packaging. From the post-test results after giving the material, there was a change in the results of 27 people, or 63%